Influencia del sistema integrado de administración financiera en la gestión de pagos de la Municipalidad Distrital de Belén 2023 - De la Cruz Vilchez, Ulices (2025)
The main problem was to study the influence of the Integrated Financial Administration System on the payment management of the District Municipality of Belén 2023. The objective of the study is to determine the influence of the Integrated Financial Administration System on the payment management of the District Municipality of Belén 2023. In relation to the objective, the quantitative study has been carried out, descriptive level with non experimental design. The most important results are related to the authorization of budget certification is carried out by the budget, 53.8% of respondents indicated that budget certification is carried out by the budgetary officer. Likewise, 100% of those surveyed indicated that the asset records are signed by those responsible for each area. It was concluded that there is a significant relationship between the influence of the integrated financial administration system in the payment management of the District Municipality of Belén 2023; given the value achieved by the Spearman Correlation Coefficient was 0.828, which indicates high positive correlation, with a vilareral significance level of 0.000.